A study on characterisation of antimicrobial resistance and antibiotic susceptibility pattern in late preterm and term neonates in a tertiary hospital, Imphal - Gurung, Bishal; Joseph, Dibin; Kambiakdik, T.; Singh, C. Shyamsunder; Singh, K. Ibochouba (International Journal of Contemporary Pediatrics, 2022)
Background: Neonatal sepsis is defined as a clinical syndrome of bacteremia with systemic signs and symptoms of infection in the first four weeks of life. It may further be divided into two main classes: early onset sepsis, which presents within the first 72 hours of birth and late onset sepsis, which usually presents after 72 hours after birth. The pattern of organisms causing neonatal sepsis has been constantly changing and the indiscriminate use of antibiotics had resulted in the emergence of multidrug resistant and virulent organisms. This study aimed to evaluate neonatal infections and the antibiotic susceptibility patterns. Methods: An institution based cross sectional study in a NICU of a tertiary care hospital. Cases enrolled were both intra and extramural who got admitted during the study period. Informed consent was obtained from the parents/guardians. Results: There were a total of 138 participants in the study. All of them tested positive for sepsis screen. Neonatal sepsis was more common in late pre-terms (57.2%) than terms (42.8%). Gram negative bacteria were the main causative agents with E. coli (9.4%) being the most common isolate followed by Acinetobacter baumanii (8%) and Klebsiella (8%). The most common gram-positive organism isolated was budding yeast cells (Candida spp.). Among gram positive bacteria the most common isolates were methicillin-resistant Staphylococcus aureus (MRSA) (5.8%) and coagulase-negative Staphylococci (CONS) (3.6%). Tigecycline and colistin were most sensitive antibiotics showing the least resistance to all organisms. Conclusions: The antibiotic sensitivity patterns have changed and the morbidity load is higher in pre-terms compared to terms.